Gumatere Dance from North Maluku as a Source of Physics Learning: Analysis of Ethnophysical Studies - Agustina Dwi Astuti, Irnin; Asep Sumarni, Ria; Setiadi, Irawan; Erdin Suhaya, Muhammad (KnE Social Sciences, 2022)
Physics is widely implemented in Maluku’s regional dances. One of these dances is the north Maluku gumatere dance. This study aimed to analyze the relationship between the concept of physical matter and gumatere dance. In the dance, there are various physical concepts, namely, momentum, impulse, GLB, sound, and elasticity. The research method used was a literature review with descriptive qualitative analysis. The data obtained were then analyzed, verified, reduced, constructed to scientific knowledge and interpreted to the concepts of physics. The results showed that the Saureka-reka dance can be used as a special physics learning resource in class X and XI SMA /MA. Regional dances can be implemented into physics lessons so that students can understand the concepts of physics well. Keywords: gumatere dance, ethnophysical, source of physics learning.